Faktor-faktor yang Mempengaruhi Produktivitas Kinerja Pegawai Pada SETDA Kabupaten Sumba Timur - Anderias Umbu Tuku Anabuni; Yonas F.Riwu; Dominikus K.T.Aman; Yuri.S.Fa’ah; Klaasvakumok.J.Kamuri; Irience R.A.manongga; Marianus S.Neno (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This research aimed at Knowing the factors influencing the employees working productivity at the Secretariat Devision of West Sumba Regency.Some variables considered as the influencing factors toward the employees working productivity (Y) in this study were the leadership style (X3),working mativation (X2),and Education and Training (X1).The sample was 60 employees taken from the population of 210 employees working as staff members at the Secretariat Division of West Sumba Regency.The Analysis namely multiple linear regresion.The results of the study indicated that the leadership style (X3),working motivation (X2),and Education and Training (X1) Influenced the employees working productivity ((Y) at the Secretariat Division West Sumba Regency.The coefficient determination was 25,9%,while the rest of 74,1% was contributed by other factors excluded in this study.